Meanings of Culture and Books. From “Marriage of Convenience” to Signs of “First Love” - Markov, Alexander (Literatūra, 2021)
The article examines the polygraphic prerequisites for social reflection of the late Soviet and post-Soviet intellectuals and the connection between the autonomy of intellectual work and the autonomy of the publishing cycle. Based on a comparison of changes in publishing technologies and procedures for preparing manuscripts for printing, the change of large paradigms in the perestroika era is reconstructed as derivatives of the cult of reading and the system of institutions that support it. It is argued that although intellectuals upheld the classical canon, the very ways of canonizing works of the past were deformed by changing publishing procedures. The crisis in publishing planning coincided with a new understanding of the intellectual’s mission, which meant the establishment of new types of reading as dominant. Thus, the thought of autonomous culture and the simultaneous reconceptualization of world literature contributed to the understanding of publishing procedures as autonomously significant. The disintegration of the disciplinary order of the Soviet publishing sphere and independent scientific book publishing made it possible to complete the project of describing literature as a place of production of norms for the reception of culture that cast doubt on the previous state of literature, thereby approving the program of post-Soviet cultural studies.